Gradient optionality in L2 acquisition at the syntax-discourse interface: Evidence from inversion in advanced and near-native English - Teixeira, Joana (Lingua, 2020)
•The syntax-discourse interface is an area of permanent optionality in L2 acquisition.•Optionality at this interface is gradient, ranging from weak to strong.•Optionality at this interface is modulated by, at least, 4 interacting factors. This article investigates the acquisition of two structures involving the syntax-discourse interface, locative inversion (LI) and there-constructions (TC), by advanced and near-native speakers of English whose L1s are European Portuguese and French. Its purpose is to test two hypotheses on the end-state of L2 acquisition at the syntax-discourse interface: the Interface Hypothesis (IH) and the L1+input Hypothesis (LIH). The former proposes that this interface is a locus permanent optionality due to processing inefficiencies related to bilingualism. The latter claims that syntax-discourse structures only generate persistent problems when they are different in the L1 and rare in the input. A battery of timed and untimed tasks tested the verbs and discourse contexts compatible with LI and TC. All L2 groups exhibited optionality regarding the phenomena tested at least in one type of task. Crucially, the control group did not display optionality in any tasks. These results indicate that, as the IH predicts, the syntax-discourse interface is an area of persistent optionality, even when the L1 is similar to the L2. They moreover suggest that optionality is gradient and influenced by, at least, four factors: construction frequency, the quantity and/or distance of the contextual information to be processed, L1-L2 (dis)similarity, and L2 proficiency.